ANALYSIS OF ADVERTISING INTENSITY ON CONSUMER CONSUMTIVE BEHAVIOR - Sudiyono Sudiyono; Abdul Aziz (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Technological developments are widely used by companies as marketing communications in introducing their products to consumers. Some of the marketing communications that can be done are through social media, television, marketplaces and websites. The role of digital marketing provides its own advantages compared to conventional marketing, this can be seen from the range given every day that can reach the wider community. This research is included in associative research where the sample used in this study amounted to 120 respondents who were taken randomly, while the analysis method used was multiple regression analysis. The results of this study obtained a value on the t test of 2,328 with a significance level of 0.028